Naringenin Inhibits Platelet Activation and Arterial Thrombosis Through Inhibition of Phosphoinositide 3-Kinase and Cyclic Nucleotide Signaling - Huang, Manting; Deng, Minzhen; Nie, Wenqiang; Zou, Dezhi; Wu, Huanlin; Xu, Danping (Frontiers in Pharmacology, 2021)
Citrus flavanoids intake can reduce the risk of cardiovascular diseases. Naringenin, a natural predominant flavonoid abundant in citrus fruits, possesses protective effects against atherothrombotic diseases. As platelet activation plays central roles in atherothrombogenesis, we studied the effects of naringenin on platelet activation, signaling, thrombosis and hemostasis. Naringenin dose-dependently inhibited agonist-induced platelet aggregation in vitro, and exhibited more-potent efficacy on ADP-induced platelet aggregation. It also suppressed platelet aggregation stimulated by ADP ex vivo. Naringenin inhibited ADP-induced platelet α-granule secretion, fibrinogen binding, intracellular calcium mobilization and platelet adhesion on collagen-coated surface. Naringenin also inhibited platelet spreading on fibrinogen and clot retraction, processes mediated by outside-in integrin signaling. Mechanism studies indicated that naringenin suppressed PI3K-mediated signaling and phosphodiesterase activity in platelets, in addition to increasing cGMP levels and VASP phosphorylation at Ser239. Furthermore, naringenin-induced VASP phosphorylation and inhibition of platelet aggregation were reversed by a PKA inhibitor treatment. Interestingly, naringenin inhibited thrombus formation in the (FeCl3)-induced rat carotid arterial thrombus model, but not cause a prolonged bleeding time in mice. This study suggests that naringenin may represent a potential antiplatelet agent targeting PI3K and cyclic nucleotide signaling, with a low bleeding risk.